Effect of prominent gas diffusion layer (GDL) on non-isothermal transport characteristics and cell performance of a proton exchange membrane fuel cell (PEMFC). (August 2015) - Perng, Shiang-Wuu; Wu, Horng-Wen; Shih, Gin-Jang
Abstract: This paper investigated the effect of prominent gas diffusion layer (GDL) on non-isothermal transport characteristics and cell performance of the proton exchange membrane fuel cell (PEMFC) by the finite-volume SIMPLE-C method coupled with preconditioned conjugate gradient methods. The geometric parameters of prominent GDL are involved in the amount ( N  = 5, 7, and 9) and the height ( H P  = 0.21, 0.31, and 0.41 mm) of prominences with the same GDL thickness for investigating the cell performance considering the effect of liquid water formation in the fluid flow field. The results show that compared with flat GDL, the prominent GDL with N  = 7 and H P  = 0.21 mm prominences enhances the cell net power best by approximately 15.07% among all geometric designs. Highlights: We study how amount and height of prominent gas diffusion layer influence PEM cell net power. Better local PEM cell power and liquid water removal are got around the GDL prominence. Prominent GDL creates stronger forced convection and enlarged contact area of reactant gas. Larger height and amount of GDL prominences has a stronger intrusion effect into channel. Maximum enhancement of cell net power is 15.07% with prominence of 7 amount, 0.21 mm height.